NYUMBA YA MUNGU RESERVOIR SYSTEM SIMULATION BY USING HEC-RESSIM MODEL - Mulungu, Deogratias M.M.; Ng ' ondya, Rejea; Mtalo, Felix W. (Tanzania Journal of Engineering and Technology, 2018)
This research paper focused on estimating effective water and optimization of the NyM reservoir for storage conservation and hydropower generation. Several models were used in the study: the Rainfall-Runoff model, GFFS was used to fill in missing data, and the HEC-ResSim Model and the NWBM for reservoir system simulation and water balance respectively. The effective inflows to the NyM reservoir were determined using HEC-ResSim model and the NWBM used to check the total water loss in the system. For the reservoir system simulation, the HEC-ResSim model was used to estimate water loss through irrigation abstractions in Kikuletwa and Ruvu reaches before water enters the NyM reservoir. The loss was estimated to be 27% of the total inflows at 1DD1 and 1DC1 gauging stations upstream the reservoir. Reservoir evaporation was estimated using pan evaporation data collected from NyM meteorological station. The effective inflows are important data to the reservoir system simulations for power production. The mean value of effective water reaching the NyM compared well with the previous study measurement of the dry season value, which was done before the dam construction. The HEC-ResSim simulated releases were used to determine the power production at NyM hydropower plant. Considering water abstractions, the first simulated alternative favored storage conservation in the reservoir. The power achieved in this alternative was 7% above the TANESCO production (41.6 GWh/yr). The second simulated alternative was to maximize power production at NyM hydropower plant. This alternative yielded 13% above TANESCO production. Despite the high energy attainable in maximization option, the reservoir water levels trend was seen to draw down drastically. The study also investigated the extent of the impact brought about by the abstracted water. If irrigation abstractions were restricted from the two reaches then power production would increase by 11.5 GWh. This increment is about 24% above the power produced when abstraction is allowed in Ruvu and Kikuletwa River reaches.